55. KNOWLEDGE AND PRACTICES ON SHARP INJURY PREVENTION AMONG HEALTHCARE WORKERS AT PHU BINH GENERAL HOSPITAL, THAI NGUYEN PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current status of knowledge and practices on occupational sharp injury prevention among healthcare workers at Phu Binh District General Hospital, Thai Nguyen province, in 2024.Methods: A cross-sectional descriptive study was conducted at Phu Binh District General Hospital from April 2024 to April 2025. A total sampling method was applied, with participation from 134 healthcare workers. Data were collected through structured interviews and observations using a pre-designed assessment tool, and analyzed with biomedical statistical algorithms.Results: The proportion of healthcare workers with adequate knowledge on sharp injury prevention was 58.0%. However, knowledge in specific areas remained low, including safe ampoule-breaking techniques (23.1%), safe handling of sharp instruments after procedures (43.3%), preventive vaccination measures (32.8%), and post-exposure protocols following sharp injuries (40.3%). In contrast, 83.6% of participants demonstrated adequate preventive practices.Conclusions: While the level of correct knowledge regarding sharp injury prevention remains limited, the overall practice performance was relatively high. There is a need for targeted interventions to enhance knowledge, especially regarding occupational sharp injury prevention among healthcare workers.
Keywords: Healthcare workers; occupational injuries; sharp instruments.